Complex treatment for dry eye disease in intermediate uveitis - E.B. Tatarnikova; O.I. Krivosheina (РМЖ "Клиническая офтальмология")
E.B. Tatarnikova, O.I. Krivosheina Siberian State Medical University, Tomsk, Russian Federation Aim: to study clinical presentations of dry eye disease (DED) in intermediate uveitis (pars planitis) and develop a complex treatment algorithm including tear substitutes, reparative, and anti-inflammatory therapies combined with laser photocoagulation. Patients and Methods: the study enrolled 98 patients divided into the study group (n=78) and the comparison group (n=20). Study group patients received complex treatment, including tear substitutes, anti-inflammatory therapies, and laser photocoagulation. Comparison group patients received topical medications only. All patients underwent a complex examination including the OSDI questionnaire, visual acuity, IOP measurements, slit lamp examination, binocular dilated fundus examination with scleral indentation, and Schirmer’s test 1 at baseline, after baseline three and six months. Treatment efficacy was assessed based on the severity of intermediate uveitis presentations. Results: intermediate uveitis exacerba tes DED. The more active chorioretinal inflammation near the ora serrata is, the more severe clinical, functional changes of the ocular surface are. Complex treatment significantly improved typical DED complaints by the OSDI score (by 34.8%), ocular surface by slit-lamp examination (lower occurrence of conjunctival fold overhang, by 51.8%), mild eyelid and conjunctival hyperemia, and conjunctival discharge. Six months after treatment, a 2-fold (vs. baseline) increase in total tear secretion and resorption of vitreous exudates and retinal edema were reported in the study group. Changes in all parameters in the study group were more significant than in the comparison group. Conclusion: complex treatment algorithm (tear substitutes, reparative, and anti-inflammatory therapies combined with laser photocoagulation) provides a more rapid and stable reduction in chorioretinal inflammation near the ora serrata. It significantly improves subjective and objective DED signs compared to conventional pharmacotherapy. Keywords: dry eye disease, intermediate uveitis, laser photocoagulation, ora serrata. For citation: Tatarnikova E.B., Krivosheina O.I. Complex treatment for dry eye disease in intermediate uveitis. Russian Journal of Clinical Ophthalmology. 2022;22(1):30–35 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-30-35.